2020
DOI: 10.1007/s42452-020-2331-1
|View full text |Cite
|
Sign up to set email alerts
|

In situ generation of silver and silver oxide nanoparticles on cotton fabrics using Tinospora cordifolia as bio reductant

Abstract: A simple, low cost and environmentally bioreduction method was adopted to in situ generate silver nanoparticles (AgNPs) on the surface of cellulose cotton fabrics utilizing Tinospora cordifolia leaf extract as reducing agent. The bio generation of AgNPs in nanocomposite cellulose cotton fabrics (NCCFs) was confirmed by Fourier Transform Infrared spectroscopy, Scanning Electron Microscopy along with Energy Dispersive X-ray (EDX) spectroscopy, X-ray Diffraction (XRD), primary and derivative thermogravimetric (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…However, a slight deviation in thermal stability is noticed for AgNPs-treated test specimens compared to the control kraft paper materials, although nanosilver loading increased the mechanical properties and UV-shielding capabilities. This phenomenon also conforms with other studies for Tinospora cordifolia extract-mediated cotton fibers functionalization with AgNPs ( Gollapudi et al, 2020 ). In DTG analysis, peaks around 300°C demonstrate hemicellulose degradation, and the peaks around 370°C correspond to cellulose from kraft fiber materials.…”
Section: Resultssupporting
confidence: 93%
“…However, a slight deviation in thermal stability is noticed for AgNPs-treated test specimens compared to the control kraft paper materials, although nanosilver loading increased the mechanical properties and UV-shielding capabilities. This phenomenon also conforms with other studies for Tinospora cordifolia extract-mediated cotton fibers functionalization with AgNPs ( Gollapudi et al, 2020 ). In DTG analysis, peaks around 300°C demonstrate hemicellulose degradation, and the peaks around 370°C correspond to cellulose from kraft fiber materials.…”
Section: Resultssupporting
confidence: 93%
“…However, the use of graft polymers as a binding agent not only involved the use of additional chemicals but also resulted in nonuniform deposition of AgNP on fabrics and a reduction in antimicrobial activity of the AgNP [ 13 , 18 ]. In situ synthesis of AgNP on fabrics by both chemical [ 19 ], as well as green routes [ 20 ], resulted in a more uniform deposition of AgNP and an increase in durability of treatment but not sufficient enough to eliminate loss of AgNP on washing [ 13 , 19 ]. The use of AgNP-treated fabrics is increasing and so is the growing concern about the negative impact of AgNP leached during washing/usage on the aquatic life [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Raghavendra et al (2013) prepared gum acacia or guar-gum-loaded cotton fibers with and without AgNPs and found that the presence of AgNPs in the fibers enhanced their tensile strength and elastic modulus (Raghavendra et al 2013). Gollapudi et al (2020) also reported the effects of AgNP synthesis on the properties of cotton fabrics (Gollapudi et al 2020). With the increase in the AgNO3 concentration, the tensile strength and elastic modulus of the cotton fabric with AgNPs also increased.…”
Section: Resultsmentioning
confidence: 99%